An effective 2D saturable absorber In2O3 to realize passively Q-switched laser output. (November 2022) - Hong, Hong; Chen, Qiudi; Wang, Yuhao; Zhang, Peixiong; Li, Zhen; Chen, Zhenqiang
Highlights: 2D In2 O3 molecular crystal was successfully prepared by CVMS for the first time. 2D In2 O3 molecular crystal was used as a saturable absorber. Q-switching at ∼1 μm is realized on Nd/Gd:YAlO3 laser. Abstract: A two-dimensional (2D) In2 O3 molecular crystal was successfully prepared by a new chemical reaction assisted vertical macro sublimation method for the first time. It was used as a saturable absorber for the first time to realize a passively Q-switching on Nd/Gd:YAlO3 solid-state laser whose emission wavelength is 1080.2 nm. The shortest pulses width is 598 ns with an average output power of 0.87 W at a repetition rate of 650 kHz, corresponding to a maximum pulse energy of 0.519 μJ. To our knowledge, this is the first experimental proof of the nonlinear absorption characteristics of 2D In2 O3 molecular crystal in Nd/Gd:YAlO3 solid-state laser, which also proves that In2 O3 -SA has great potential for light modulator in ∼1 μm spectral region. The results will promote the development of two-dimensional materials and further explore their potential applications in the field of ultra-fast photonics.